Associations of psychosocial and physical work demands with all-cause mortality: a pooled analysis of prospective cohort studies - Tanjung, Kamilia; K. C., Prakash; Kyrönlahti, Saila; Goldberg, Marcel; Nygård, Clas-Håkan; Neupane, Subas (Oxford University Press, 2025)
Background
The findings regarding mortality risk attributable to psychosocial and physical work demands are inconsistent. Pooled estimates using participant-level data from multiple cohort studies may provide more conclusive evidence.
Methods
Four prospective cohort studies conducted in England, Finland, France, and the USA were used (age 36–62 years; n = 41 760). We studied 34 903 and 36 076 individuals who had baseline (1981–2005) information on self-reported psychosocial and physical work demands, respectively. All-cause mortality until the year 2018 was ascertained through linkage to national registers, National Death Index, and company databases. We investigated the associations of psychosocial and physical demands with all-cause mortality separately for females and males using Cox regression models that were adjusted for socio-demographic and lifestyle factors. Using random-effects meta-analysis, we calculated pooled estimates of all-cause mortality for moderate and high exposure levels.
Results
During the mean follow-up of 25 years, 2105 deaths occurred among females and 5048 deaths occurred among males with information on psychosocial demands. The corresponding numbers for those with information on physical demands were 2176 and 5101. Fully adjusted models indicated that psychosocial demands were associated with both lower and higher all-cause mortality risks in both sexes. Physical demands increased the risk of all-cause mortality in both sexes and the association was strongest among males with moderate exposure levels (pooled hazard ratio 1.10, 95% confidence interval 1.02–1.19).
Conclusion
The relationship between psychosocial work demands and all-cause mortality remains inconclusive, whereas moderate physical work demands increase the mortality risk among males.